2000
DOI: 10.1023/a:1008979417618
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: These results suggest that polymorphic variation in or near the 3' end of the VDR gene influences breast cancer risk in Latina women.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
30
1
1

Year Published

2000
2000
2012
2012

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 114 publications
(34 citation statements)
references
References 32 publications
2
30
1
1
Order By: Relevance
“…These data encouraged several study groups to enlarge the investigations with regard to breast cancer. Two studies revealed a 4-fold higher risk of metastatic spread in breast cancer patients showing the Bsm I restriction site in the VDR gene [12, 13]. The aa genotype indicates a significantly increased risk of developing breast cancer [17].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These data encouraged several study groups to enlarge the investigations with regard to breast cancer. Two studies revealed a 4-fold higher risk of metastatic spread in breast cancer patients showing the Bsm I restriction site in the VDR gene [12, 13]. The aa genotype indicates a significantly increased risk of developing breast cancer [17].…”
Section: Discussionmentioning
confidence: 99%
“…The allelic variations are indicative of an increased risk of breast cancer. Furthermore, breast cancer patients with a particular VDR genotype have an increased risk of lymph node involvement of the tumor or occult metastases [11, 12, 13]. However, in none of the studies performed so far, the likelihood of developing bone metastases has been associated with a specific VDR genotype.…”
Section: Introductionmentioning
confidence: 99%
“…One example includes BsmI restriction site polymorphisms, which occur in the intron separating exons VIII and IX, and are linked with another polymorphism, a poly(A) microsatellite located in the 3 0 UTR (Ingles et al, 2000). The BB genotype has been associated with higher circulating 1,25(OH) 2 D levels , and with lower risk of breast cancer in some (Yamagata et al, 1997;Ruggiero et al, 1998;Bretherton-Watt et al, 2001) but not all (Ingles et al, 2000;Hou et al, 2002) studies. Findings for colon cancer (Slattery et al, 2001) and prostate cancer (Ingles et al, 1997) also support a potential protective effect of this polymorphism or haplotypes containing this polymorphism.…”
Section: Gene-diet Interactionsmentioning
confidence: 99%
“…However, prostate cancer cells display a spectrum of sensitivities to the antiproliferative action of 1a,25(OH) 2 D 3 (reviewed in Chen and Holick (2003), Krishnan et al (2003) and Peehl and Feldman (2003)). Reflective of an antiproliferative role, epidemiological studies have now linked the incidence of prostate cancer to low serum levels of 25(OH)D 3 as a result of either diet or environment, and specific VDR polymorphisms have been correlated with cancer susceptibility (Hanchette and Schwartz, 1992;Ingles et al, 1998). Collectively, such data implicate 1a,25(OH) 2 D 3 with a protective action against uncontrolled prostate growth; that initiation or progression of prostate cancer may relate to reduced dietary intake and/or cellular resistance to the antiproliferative effects of 1a,25(OH) 2 D 3 .…”
Section: Introductionmentioning
confidence: 99%